Youth Brain Influence Improves Children's Learning Concentration In Tosaren Elementary 4 Kediri City - Marten Ndapajaki; Aprin Rusmawati; Alfian Fawzi (Universitas STRADA Indonesia, 2021)
Giving Brain Gym to children is an effective step to facilitate learning activities and adjustments to daily activities in improving views on the material explained by the teacher and can help optimize brain function. The purpose of this study was to determine the effect of Brain Gym in Improving Learning Concentration in Children at SD N Tosaren 4, Kediri City. This research design uses a quasi-experimental design ( Quasi Experiment Design ), namely the Non-Equivalent Control Group design . The sampling technique is total sampling. The sample in this study were all 5th grade students of SDN Tosaren 4, Kediri City, totaling 30 children. The independent variable to be studied is Brain Gym and the dependent variable is learning concentration. The statistical test used is Wilcoxon. The results of the study showed that learning concentration before being given brain gymnastics treatment ( Brain Gym) was lacking, namely 19 children (63%) out of a total of 30 children, while learning concentration after being given brain gymnastics treatment (Brain Gym) was good, namely 25 children (83%) out of a total of 30 children. The results of the statistical test showed the Asymp. Sig. value. (2-tailed) before and after is 0.000 so that H1 is accepted meaning there is an effect of Brain Gym stimulation on the concentration of learning of children of SDN Tosaren 4 Kediri City. From the results of the study, Brain Gym is very helpful for children in increasing their concentration to learn. Brain gymnastics can be given in the classroom when children start to get bored with the long delivery of material.